1981
DOI: 10.1002/art.1780240708
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary ferrographic survey of the wear particles in human synovial fluid

Abstract: The technique of ferrography has been applied to the analysis of wear particles in human synovial fluid aspirates. A number of discrete, identifiable classes of wear particles were found, including particles indicative of cutting wear and rubbing wear. The spectrum of particles varied among different groups of patients, suggesting an eventual diagnostic use for this method.No reliable method exists for the early diagnosis of degenerative arthritis. Present diagnoses rely upon radiographic or clinical data whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Increased cartilage wear, leading to formation of loose particles in the joint space, has been linked to aging, overuse and obesity 2 , often leading to osteoarthritis (OA). Several studies have investigated using synovial fluid aspirates to diagnose OA by characterizing cartilage wear particles in the synovial joint 35 . Clinically, it has been observed that cartilage and bone debris are bound to the surface or embedded deep within the synovial membrane of patients suffering from capsular synovial hyperplasia and metaplasia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased cartilage wear, leading to formation of loose particles in the joint space, has been linked to aging, overuse and obesity 2 , often leading to osteoarthritis (OA). Several studies have investigated using synovial fluid aspirates to diagnose OA by characterizing cartilage wear particles in the synovial joint 35 . Clinically, it has been observed that cartilage and bone debris are bound to the surface or embedded deep within the synovial membrane of patients suffering from capsular synovial hyperplasia and metaplasia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Kitridou et a1 demonstrated collagen in 10 of 18 fluids from OA joints and in 1 of 5 fluids from RA joints, using electron microscopy and hydroxyproline assay after acid hydrolysis (15). Other investigators have demonstrated a correlation between articular lesions detected by arthroscopy and identification of cartilage fragments in SF, and have advocated the potential diagnostic use of such analyses (16,17). Cheung et al, using sodium dodecyl sulfatepolyacrylamide gel electrophoresis and spectrophotometric scanning, demonstrated collagen in 12 of 17 pellets prepared from fluid aspirates from 17 knee joints of patients with various forms of arthritis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Particles need to have a positive volumetric magnetic susceptibility of the order of 50 Â 10 À 6 or more to be deposited in ferrography. This approach was applied to prepare wear particles found in synovial fluid to study wear in human knee joints [4,[83][84][85][86][87][88]. Wear particles found in human knee joints do not have positive magnetic susceptibility.…”
Section: Preparation Techniques Of Biological Wear Particlesmentioning
confidence: 99%